Problems in Translation: The Case of EFL Learners in Translating Cultural Texts - Sri Widyarti Ali; Nurlaila Husain; Helena Badu; Irmawaty Umar (Ideas Publishing, 2022)
Translation is the process of transferring information from one language to another. Due to the fact that it requires proficiency in two languages, EFL students often encounter problems and difficulties during the translation process. To elucidate that fact further, this study examined students problems translating cultural texts, both from Indonesian to English and vice versa. The research data were gathered from students translation documents and source language texts, as well as from a questionnaire, in order to delve deeper into the problems students face when translating written text. The data analysis process was carried out through three stages as suggested by Miles & Huberman (1994, p: 10); reducing the data, explaining the data, and taking a conclusion. Reducing data is a process of selecting, focusing, simplifying and abstracting the data. Explaining the data is a process of organizing information and arranging the complete narration. Taking a conclusion is the process of drawing conclusions from the data. The main theory used in the process of collecting and analyzing data is the theory of translation problems proposed Alan Duff (1989) which consists of the problems of pragmatic, cultural, linguistic, and text-specific. The research result reveals some problems that the majority of students have in translating the texts, either from Indonesian into English or English into the Indonesian language. In translating the text of Indonesian into English, most of the students have problems with pragmatic aspects, in which they get difficulty finding and determining which equivalents correspond to the context of the source text. They, moreover, have problem in linguistics, such as the problems of grammar, syntax, and semantics. While in translating the text of English into Indonesian, most of them encounter the problems of pragmatics and semantics. The outcome of this study is expected to provide students with information on how to avoid and overcome difficulties encountered while translating texts, particularly those related to culture, and to serve as a guide for lecturers in developing syllabi and planning learning activities for translation courses. Penerjemahan adalah proses mentransfer informasi dari satu bahasa ke bahasa lain. Karena membutuhkan kemahiran dalam dua bahasa, mahasiswa masih sering mengalami masalah dan kesulitan dalam proses penerjemahan. Untuk mengungkap fakta tersebut, penelitian ini bertujuan untuk mengeksplorasi permasalahan mahasiswa dalam menerjemahkan teks tulis, baik dari bahasa Indonesia ke bahasa Inggris, maupun dari bahasa Inggris ke bahasa Indonesia. Data penelitian diperoleh melalui dokumen terjemahan siswa dan teks bahasa sumber, serta angket untuk menggali lebih dalam permasalahan yang dihadapi siswa dalam menerjemahkan teks tulis. Proses analisis data dilaksanakan melalui tiga tahapan sebagaimana dikemukakan oleh Miles & Huberman (1994, p:10): (1) mereduksi data, (2) menjelaskan data, dan (3) menyimpulkan. Reduksi data adalah proses memilih, memfokuskan, menyederhanakan, dan mengabstraksi data. Menjelaskan data adalah proses mengorganisasikan informasi dan menarasikan secara utuh. Mengambil kesimpulan adalah proses menarik kesimpulan dari data. Teori utama yang digunakan dalam proses pengumpulan dan analisis data adalah teori tentang masalah penerjemahan dari Alan Duff (1989) yang terdiri dari masalah pragmatik, budaya, linguistik, dan text-specific. Hasil penelitian mengungkapkan beberapa permasalahan yang dihadapi sebagian besar mahasiswa dalam menerjemahkan teks, baik dari bahasa Indonesia ke bahasa Inggris atau bahasa Inggris ke bahasa Indonesia. Dalam menerjemahkan teks bahasa Indonesia ke bahasa Inggris, sebagian besar mahasiswa mengalami masalah pragmatik, di mana mereka mengalami kesulitan untuk menemukan dan menentukan padanan kata yang paling sesuai dengan konteks bahasa sasaran. Selain itu, mereka juga menghadapi masalah linguistik, seperti masalah tata bahasa, sintaksis, dan semantik. Sedangkan dalam menerjemahkan teks bahasa Inggris ke bahasa Indonesia, sebagian besar mengalami masalah pragmatik dan semantik. Hasil penelitian ini diharapkan dapat memberikan informasi bagi mahasiswa untuk menghindari dan mengatasi permasalahan yang mungkin dihadapi dalam proses penerjemahan teks, serta dapat menjadi pedoman bagi dosen dalam merancang silabus dan merencanakan kegiatan pembelajaran mata kuliah penerjemahan.